Abstaining from alcohol and labour market underperformance: Have we forgotten dry alcoholics? - Edvard Johansson (The Research Institute of the Finnish Economy (ETLA), 2004)
Prior research on the relationship between alcohol consumption and labour market success has generally found that abstainers do worse on the labour market than moderately drinking individuals. Some authors have argued that these results are consistent with medical research finding that moderate alcohol consumption is associated with improved health, and that this improved health also carries over to improved labour market success. However, very seldom, if ever, has attention been paid to the fact that a part of the abstainers are ex-alcoholics, who have quit drinking owing to alcohol problems. In this paper we show, using the new Finnish “Health 2000” dataset, that the underperformance of abstainers in a labour market sense is almost entirely due to the fact that some abstainers are ex-drinkers who have been diagnosed with alcoholism. Finnish men who have never drunk alcohol are not doing worse than drinkers. – Alcoholism ; Abstinence ; Work probability
Keywords: I12; J69; 330; Alkoholkonsum; Arbeitsmarkt; Finnland